Building the Legitimacy of Whistleblowers: A Multi‐Case Discourse Analysis1. (20th December 2018) - Stolowy, Hervé; Gendron, Yves; Moll, Jodie; Paugam, Luc
ABSTRACT: Evidence suggests that society still does not view whistleblowers as wholly legitimate—despite legal protections now offered in some jurisdictions, such as the United States. Drawing on a discourse analysis (i.e., an examination of statements), we investigate the well‐publicized stories of seven whistleblowers from 69 sources, including books, first‐ and second‐hand interviews, websites, and videos. Our focus is to examine how whistleblower discourses can build legitimacy by more tightly defining the whistleblower role and demonstrating its alignment with social norms. Using whistleblower self‐narratives, we identify four narrative patterns: (i) Trigger(s)—the event(s) leading to whistleblowing; (ii) Personality traits—whistleblower's morality, resourcefulness, and determination; (iii) Constraints—barriers requiring regulatory and organizational change; and (iv) Consequences—the longer term positive impact of the whistleblowing act. These patterns rely on symbolic, analogical, and metaphorical framing to allow others to better understand the role of whistleblowers and enlist their support. Exploring a data set of 1, 621 press articles, we find indications that these narrative patterns resonate in the media—which provide a form of support and may be instrumental in legitimizing the whistleblower role. Grounded on these results, we develop a legitimacy construction model of the whistleblower role, that is, a representation of how role legitimacy is produced and sustained. From this model, we identify a number of important areas for future research.